Legal Problems The Implementation Of Credit Agreements With Fiduciary Guarantees - Febriana, Anggita; Sentot Sudarwanto, Albertus; Elok Puri Maharani, Andina (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This look at targets to analyze the legal problems with the implementation of Credit Agreements, especially in relation to the credit using fiduciary guarantees as collateral. Financing institutions use Credit Agreements that are included in the Standard Agreement. Because credit is a business activity of financial institutions, in this case it is a bank, in order to achieve a national balance in distributing funds to the public. In carrying out its function, banks as financial institutions provide credit, therefore the provisions of the Guarantee Law are intended to help business activities both macro and micro, as well as create legal certainty for stakeholders. To achieve the goal of obtaining legal certainty regarding Credit Agreements with Fiduciary Guarantees, This study uses an empirical legal approach method, and the research specifications are descriptive analytical.This study produced a data, namely it was concluded that Fiduciary Guarantee is a form of guarantor by the debtor at his request, in order to guarantee the repayment of credit debts, movable objects become the object of guarantee in this study. The Supplementary Agreement or what is often referred to as the Accesoir of the Principal Credit Agreement can be guaranteed by the Fiduciary Guarantee, while the charge is made in the form of a notarized, by guaranteeing legal certainty so that it needs to be Register with the Trustee Registration Authority and apply for issuance of a Trustee Certificate to gain enforcement powers. The obstacle arises when defaulting by the debtor, with various causes and factors. Sometimes execution efforts are made to save credit that has been channeled by financing institutions, especially banks, but in practice there are many obstacles, including in executing the object of the guarantee that is not found, has changed hands or is controlled by others, so that execution in the form of auctioning fiduciary objects is difficult to do.